Young People: Between Literature and Advanced Technologies - Asmaradhani, Ahmad Idris (Journal of Language Learning and Research (JOLLAR), 2017)
In the eyes of literature, existentialist thinkers focus on the question of concrete human existence and the conditions of this existence rather than hypothesizing a human essence, stressing that the human essence is determined through life choices. The ideal, however, is that humans exist in a state of distance from the world that they nonetheless remain in the midst of. This distance is what enables humans to project meaning into the disinterested world of in-itselfs. This projected meaning remains fragile, constantly facing breakdown for any reasonâ from a tragedy to a particularly insightful moment. In such a breakdown, humans are put face to face with the naked meaninglessness of the world, and the results can be devastating. It is porposed that literature and the media combined have a powerful impact on those who wish to truly realize and understand their message. By studying, reading, learning, experiencing, and knowing the culture of the present and those cultures of the past then one can understand the ideas of life and how the two work together to help us better understand each other and ourselves. In what ways our present culture, our technological advances, and the media shape who we are as individuals is not a simple question. The answer seems to elusively hide in a world filled with cultural complexities. But, it is no secret to find that literature is a source of power. It does influence, guide, and shape the human become as they continue their journey through life. Hence, since human are never without the influence of literature, they will always have factors working to modify the human being. However, it is their choice as to how they internalize what they are exposed to, and in turn, it is up to them to determine the individual that ultimately prevails.